(untitled) (Psychology Travelogs, 2023)
The article presents the peculiarities of professional burnout of servicemen of the engineering troops of the Armed Forces of Ukraine. The empirical results of the study of burnout in professions with an increased risk of early development of its symptoms on the example of military personnel of the engineering troops of the Armed Forces of Ukraine are discussed. Approaches to the development of prevention of their burnout are substantiated. The presented results of the study make it possible to consider the prevention of mental health of a professionally active serviceman as one of the important tasks of forming his ability to achieve his own success in interaction with others, and the content of health psychology is thereby transferred to the plane of humanistic and positive psychology, where the main value is the ability to active self-realization of the individual included in a variety of social relations. Therefore, the prevention of professional health and burnout among managerial personnel of engineering troops should be aimed at revealing and supporting personal resources of coping behavior. At the same time, an important aspect is to increase the level of responsibility for one’s subordinates, which, in combination with the ability to make decisions in difficult situations, is the basis of the professional competencies of a military leader. Prevention of professional health and the threat of burnout in the personnel of the engineering troops should be aimed at strengthening the sense of significance of their work, awareness of their own involvement in its results (a sense of coherence or connectivity of the individual with the environment).